2022
DOI: 10.1016/j.puhe.2021.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Perceived changes in lifestyle behaviours and in mental health and wellbeing of elementary school children during the first COVID-19 lockdown in Canada

Abstract: Objectives The closure of schools to prevent the spread of COVID-19 prompted concerns of deteriorating lifestyle behaviours, mental health, and wellbeing of children, particularly those in socioeconomically disadvantaged settings. We assessed changes in lifestyle behaviours (physical activity, screen time, eating habits and bed/wake-up times), mental health and wellbeing during the first lockdown in Spring 2020 as perceived by school children from disadvantaged settings, and examined determinants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 43 publications
1
15
1
3
Order By: Relevance
“…With later bedtime, longer sleep latency, later sleep onset and later sleep midpoints, this suggests a pattern of a rearward shift of sleep period during both school days and non-school days, even though only an increase in sleep latency survived correction for multiple comparisons. Our findings extended the current literature that children and adolescents not only had delayed sleep in the first months of the pandemic (18)(19) by demonstrating enduring changes in sleep-wake patterns over the first 15 months of COVID. It is not surprising that secondary school students are affected more than primary school students, as adolescents are more prone to insomnia and sleep phase delays than younger children (6)(9).…”
Section: Discussionsupporting
confidence: 87%
“…With later bedtime, longer sleep latency, later sleep onset and later sleep midpoints, this suggests a pattern of a rearward shift of sleep period during both school days and non-school days, even though only an increase in sleep latency survived correction for multiple comparisons. Our findings extended the current literature that children and adolescents not only had delayed sleep in the first months of the pandemic (18)(19) by demonstrating enduring changes in sleep-wake patterns over the first 15 months of COVID. It is not surprising that secondary school students are affected more than primary school students, as adolescents are more prone to insomnia and sleep phase delays than younger children (6)(9).…”
Section: Discussionsupporting
confidence: 87%
“…Un estudio longitudinal mostró que el estilo de vida en general empeoró en los últimos siete meses después del bloque en España, y las variables asociadas fueron ser trabajador esencial, menor nivel educativo, enfermedad mental previa y peor salud autoevaluada, así como cambios en el sueño y la alimentación (Cervera-Martínez et al, 2021). En Canadá se evaluó los estilos de vida en niños de primaria, se encontró una disminución en la actividad física, tener horarios para dormir / despertarse tarde, así como un aumento en el tiempo frente a la pantalla y los refrigerios (Maximova et al, 2021). Un estudio sistémico encontró prevalencia de estrés psicosocial o mental, un aumento de peso y disminución de la actividad física, así como la cantidad y calidad de sueño (Rawat, Dixit, Gulati, Gulati y Gulati, 2021), la actividad física, el ejercicio, el tabaquismo y el consumo de alcohol, así como el IMC previo al bloqueo, fueron predictivos de cambios de peso durante el confinamiento en Alemania (Palmer, Bschaden y Stroebele-Benschop, 2021).…”
Section: Impacto De La Pandemia En Los Estilos De Vidaunclassified
“…Moreover, there was sharp decline in MVPA during COVID-19 pandemic [ 16 ], reducing the amount of adolescents meeting the current physical activity recommendations [ 17 ]. Whether confirmed that higher physical activity leads to lower health care costs in adolescents, this relationship is even more concerning in a post-pandemic scenario in which a marked decline in MVPA [ 18 , 19 ] prove long-lasting after schools and athletic programs resume.…”
Section: Introductionmentioning
confidence: 99%